Desain Lanskap Taman Dipangga sebagai Taman Sejarah dan Rekreasi berbasis COVID-19 - Hetharia, Bartholomew Jordan; Franjaya, Eduwin Eko (Jurnal Arsitektur Lansekap, 2023)
Landscape Design of Taman Dipangga as a Historical and Recreational Park based on COVID-19 . Taman Dipangga is a city park with a strategic location and easy access. In the middle of the COVID-19 pandemic crisis, city parks, which are part of open public spaces, should be resilient and adaptive to the current situation. Taman Dipangga, likewise, must adapt to the current situation in terms of design and amenities. As one of the cultural and historical attractions in Bandar Lampung, Taman Dipangga has the potential to become one of the favorite tourist destinations for visitors. This research aims to design Taman Dipangga by highlighting the historical aspects as well as the recreational components that are responsive to COVID-19. This qualitative research was conducted using the survey method, which included observation, interview, and literature review that refers to the design process. This research leads to the use of historical and recreational concepts in Taman Dipangga to optimize the potential of Taman Dipangga by representing it through the Krakatau Monument, the form of design, the division of space and its naming, as well as the selection of vegetation based on the condition of the location on Mount Krakatau and the surrounding area. Taman Dipangga will be more than just a recreation park; it will also be a place for education and a cultural heritage site.